Technical Efficiency of Thermal Power Generation in India: Post-Restructuring Experience - Fatima, Sahba; Barik, Kaustuva (International Journal of Energy Economics and Policy, 2012)
The Indian power generation industry has undergone a paradigm shift during the past two decades largely due to private sector participation and restructuring of the sector. In order to assess the performance of the power generation sector, the present study takes annual data of 14 major states in India for the period 2000-01 to 2007-08 and estimates a stochastic translog production frontier. The decline in technical efficiency of the Indian power generation sector over the study period, as obtained from the econometric estimation, appears to indicate that it has failed to bring in the desired results in terms of efficiency improvement. The total factor productivity (TFP) of the power generation industry, which includes technical change, technical efficiency change, and scale change, however, has shown some improvement. Technical efficiency of the power generation industry is explained by technical manpower employed, per capita state domestic product, year of unbundling of State Electricity Boards (SEBs) and time variable. The study concludes that inefficiency in Indian power sector is caused by the above mentioned factors rather than stochastic error. Keywords: Stochastic Frontier Analysis; Power Sector Reforms; Total Factor Productivity; India JEL Classifications: D24; L94; O13